Knowledge, Attitude, and Practice of Family Planning among Currently Married PAHARI Cast Women in Nepal: Case Study of Panauti-10, Khopasi, Kavre District - Kafle, Rameshwor (Ganeshman Darpan, 2022)
Family planning contributes to improving health and ensuring access to adequate food, clothing, housing, and educational opportunities for people. This study simply tried to analyze the “Knowledge, Attitude and Practice of family planning among PAHARI cast women” with respect to socio-economic condition of the sample size of the population in the study area. The study found that knowledge of at least one modern method of family planning is almost universal among currently married PAHARI cast women. This study found more than 98 percent PAHARI has knowledge of at least one family planning method but the users are only 62.7 per cent of any method and the modern method family planning users are only 60 per cent. These finding figures clear the low-use patterns of family planning devices in the study population of the study area.